Pengaruh Film Drama Korea Terhadap Penggunaan Bahasa Mahasiswa Fkip Universitas Muhadi Setiabudi Brebes (Kajian Sosiolinguistik) - Ika Nurhayati; Prasetyo Yuli Kurniawan; Hany Uswatun Nisa (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study reviews the influence of Korean drama films on the language use of Muhadi Setiabudi Brebes University students, (sociolinguistic research). The purpose of this research is to recognize whether Korean drama films influence the use of language of FKIP students of Muhadi Setiabudi Brebes University which becomes bilingulism. This type of study is a combination procedure, which mixes 2 procedures, qualitative procedures and quantitative procedures. The sources of information used in this study are: 1) primary information and 2) secondary information. The procedures for collecting information used in this study are: 1) literature research 2) field research. The results of the study showed that there was an influence of Korean drama films on the language use of FKIP students of Muhadi Setiabudi Brebes University with an influence of 67.6%, which means that variable X has a significant influence on variable Y. The results of this study show that the Null Hypothesis( Ho) is rejected and the working hypothesis ( Ha) is accepted, namely the influence of Korean drama films on the language use of Muhadi Setiabudi Brebes University students. The form of using FKIP students who watch Korean drama films is to become bilingualism.